Prevalence and antimicrobial susceptibility pattern of gram-negative bacteria contaminating the hands of patients’ visitors at regional referral hospitals in Dar-es-Salaam - Ninael Jonas; Donath Mkenda Valerian; Stanslaus Henry; Emmanuel Magembe; Reuben Abednego; Loveness Urio; Eligius Lyamuya (PLoS ONE, 2025)
Background Hand contamination by bacteria is a significant source of infection transmission, especially in hospital settings. A healthcare-associated infection is one that a person contracts as a result of their interaction with a hospital. Health care workers’, patients’ and visitors’ hands are all transmission routes for infections, in particular bacterial infections. These infections elevate the economic burden on healthcare systems especially in low-income settings. Objective To determine the prevalence of gram-negative bacteria hand contamination among patients’ visitors of referral hospitals in Dar es Salaam. Methodology This was a cross-sectional study conducted at 3 regional referral hospitals: Amana, Temeke and Mwananyamala in March 2023. Dominant hand swabs from 388 systematically selected visitors were taken for bacterial culture and a short interview was conducted to assess factors associated with Gram-negative bacterial hand contamination. Hand swabs collected were cultured on Mac Conkey Agar (MCA), isolates were identified by VITEK MS and appropriate antibiotics were employed in antibiotic susceptibility testing of the isolated Gram-negative bacteria. Results Prevalence of gram-negative bacterial contamination on visitors’ hands was 91 (21.1%) on entry and 103 (30.2%) on exit. The most common bacteria contamination was from Klebsiella pneumoniae on both entry and exit points, 37 (41%) and 57 (43%) respectively. Resistance to cephalosporins (Cefotaxime and Ceftriaxone) were the most pronounced. Proportion of ESBL-producing bacteria was significantly higher at exit than at entry. Bacterial contamination was associated with not washing hands APR = 1.5 (95% CI:1.03-2.17), offering services to the patient APR = 1.9 (95% CI:1.21-2.87) and longer hospital stays (more than 7 days) APR = 1.5 (95% CI:1.1-2.0). Conclusion To prevent the transmission of bacteria, it is important to emphasize hand hygiene and exposure limits for visitors entering hospital environments.